Determination of the Needs of Students by Psychological and Pedagogical Teaching Tools Using Remote Technologies - Shamuratova Malika Shadjalilovna; Kiyasova Ra’no Malikovna; Sidiknazarova Zulfiya Mirsharapovna; Amanov Alisher Kakhramonovich (Zien Journals, 2022)
Within the framework of the article, the problem of using modern distance (digital) technologies in online learning of students of educational organizations is considered. The study examines the psychological and pedagogical features of the electronic educational environment and its impact on the satisfaction of students' needs. The study sample included students aged 19 to 24 in the amount of 42 people. The main research methods were: observation, conversation, questioning, analysis, mathematical methods of data processing. In the course of the study, it was possible to establish the relationship between the educational environment (traditional and innovative) and the types of needs that find their satisfaction
Keywords: traditional; students; digital and online learning; innovative learning environments